2017
DOI: 10.1038/s41598-017-05601-9
|View full text |Cite
|
Sign up to set email alerts
|

Activated Monocytes Enhance Platelet-Driven Contraction of Blood Clots via Tissue Factor Expression

Abstract: Platelet-driven reduction in blood clot volume (clot contraction or retraction) has been implicated to play a role in hemostasis and thrombosis. Although these processes are often linked with inflammation, the role of inflammatory cells in contraction of blood clots and thrombi has not been investigated. The aim of this work was to study the influence of activated monocytes on clot contraction. The effects of monocytes were evaluated using a quantitative optical tracking methodology to follow volume changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 53 publications
2
20
0
2
Order By: Relevance
“…Once monocytes are exposed to quantities of a tissue factor, they may bind to platelets and increase MPAs 37 resulting in enhanced clot contraction to cause thrombosis. 38 In our current study, we found P-selectin expressed on the surface of platelets that interact with monocytes. However, we unexpectedly found that the numbers of circulating MPAs had no significant difference between CCS and ACS subjects.…”
Section: Discussionsupporting
confidence: 48%
“…Once monocytes are exposed to quantities of a tissue factor, they may bind to platelets and increase MPAs 37 resulting in enhanced clot contraction to cause thrombosis. 38 In our current study, we found P-selectin expressed on the surface of platelets that interact with monocytes. However, we unexpectedly found that the numbers of circulating MPAs had no significant difference between CCS and ACS subjects.…”
Section: Discussionsupporting
confidence: 48%
“…There is emerging indirect evidence that the degree and the rate of contraction of clots and thrombi may be an important pathogenic factor that affects the local blood hydrodynamics and the outcome of thrombosis. 4 17 18 25 Although the severity of thrombosis is largely determined by size and location of the occluded vessel, the ability of the clot to contract more or less can largely influence the vessel cross-sectional area and consequently the blood flow through the vessel and the shear rate of the blood. This has implications for the possibility of embolization, where shear rate coupled with the structure of the clot could influence the predisposition to embolize based on either mechanical and/or enzymatic disintegration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in previous studies that monocytes carry TF, which is responsible for their procoagulant effect. 52 Under physiological conditions, monocytes are inactivated and do not express TF. When activated in a pathological context, they acquire TF expression.…”
Section: Discussionmentioning
confidence: 99%